THE INFLUENCE OF LEADERSHIP STYLE, PHYSICAL ENVIRONMENT, NON-PHYSICAL ENVIRONMENT, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE DINAS SOSIAL KOTA BATU - Hartono (Pusat Pengkajian dan Pengembangan Sumber Daya Manusia (P3SDM) Melati, 2021)
One of the dynamic goals of an organization is to ensure that its employees are able to work according to the targets set or that employees have a good performance. However, there are several factors that can affect the level of employee performance, including the leadership style applied by the leader, the physical and non-physical conditions in which the employee works, and the employee’s commitment to the organization. The purposes of this research were to determine: (1) the effect of leadership style on employee performance, (2) the effect of the physical environment on employee performance, (3) the effect of the non-physical environment on employee performance, and (4) the effect of organizational commitment on employee performance. This research used quantitative method with an associative design. The population in this research was 32 employees at Dinas Sosial Kota Batu. The sampling technique in this research used total sampling, so that the entire population is determined to be the sample. The data collection process in this research used questionnaire and documentation techniques. The data analysis technique in this research used multiple linear regressions analysis through SPSS version 23.0. Based on the results of research and data analysis, it can be concluded as follows: (1) Leadership style has a positive and significant effect on employee performance at Dinas Sosial Kota Batu, (2) the physical environment has a positive and significant effect on employee performance at Dinas Sosial Kota Batu, (3) the non-physical environment has a positive and significant effect on employee performance at Dinas Sosial Kota Batu, (4) organizational commitment has a positive and significant effect on employee performance at Dinas Sosial Kota Batu.